ESTIMATED RESERVES AND ESTIMATED LIABILITIES: THE PROBLEM OF INTERPRETATION IN THE SYSTEM OF RUSSIAN LEGAL REGULATION OF ACCOUNTING - O. V. Zhukova (Publishing House of the State University of Management, 2020)
The Russian legal framework for accounting of estimated reserves and estimated liabilities of commercial organizations for the existing terminology space, the problems of correlation of the economic essence of these accounting categories and current legislation, the value of correct application of terminology in accounting (financial) statements for a wide range of stakeholders has been analysed. Special attention has been paid to the distinctive features of estimated reserves and estimated liabilities in the prism of their economic essence. Based on the results of the study, proposals regarding the interpretation of the concepts of “estimated reserve” and “estimated liability” in the implementation of the program to reform the Russian system of legal regulation of accounting and preparation of accounting (financial) statements have been formulated.